Development of a marker panel for genotyping of domestic soybean cultivars for genes controlling the duration of vegetation and response to photoperiod - R. N. Perfil’ev; A. B. Shcherban; E. A. Salina (Вавиловский журнал генетики и селекции, 2021)
Soybean, Glycine max L., is one of the most important agricultural crops grown in a wide range of latitude. In this regard, in soybean breeding, it is necessary to pay attention to the set of genes that control the transition to the flowering stage, which will make it possible to adapt genotypes to local growing conditions as accurately as possible. The possibilities of soybean breeding for this trait have now significantly expanded due to identification of the main genes (E1–E4, GmFT2a, GmFT5a) that control the processes of flowering and maturation in soybean, depending on the day length. The aim of this work was to develop a panel of markers for these genes, which could be used for a rapid and efficient genotyping of domestic soybean cultivars and selection of plant material based on sensitivity to photoperiod and the duration of vegetation. Combinations of 10 primers, both previously developed and our own, were tested to identify different alleles of the E1–E4, GmFT2a, and GmFT5a genes using 10 soybean cultivars from different maturity groups. As a result, 5 combinations of dominant and recessive alleles for the E1–E4 genes were identified: (1) e1-nl(e1-as)/ e2-ns/e3-tr(e3-fs)/e4; (2) e1-as/e2-ns/e3-tr/E4; (3) e1-as/e2-ns/E3-Ha/e4; (4) E1/e2-ns/e3-tr/E4; (5) e1-nl/e2-ns/E3-Ha/E4. The studied cultivars contained the most common alleles of the GmFT2a and GmFT5a genes, with the exception of the ‘Cassidi’ cultivar having a rare dominant allele GmFT5a-H4. The degree of earliness of cultivars positively correlated with the number of recessive genes E1–E4, which is consistent with the data of foreign authors on different sets of cultivars from Japan and North China. Thus, the developed panel of markers can